Cancer: an emergent property of disturbed resource‐rich environments? Ecology meets personalized medicine. (26th March 2015) - Ducasse, Hugo; Arnal, Audrey; Vittecoq, Marion; Daoust, Simon P.; Ujvari, Beata; Jacqueline, Camille; Tissot, Tazzio; Ewald, Paul; Gatenby, Robert A.; King, Kayla C.; Bonhomme, François; Brodeur, Jacques; et al.
Abstract For an increasing number of biologists, cancer is viewed as a dynamic system governed by evolutionary and ecological principles. Throughout most of human history, cancer was an uncommon cause of death and it is generally accepted that common components of modern culture, including increased physiological stresses and caloric intake, favor cancer development. However, the precise mechanisms for this linkage are not well understood. Here, we examine the roles of ecological and physiological disturbances and resource availability on the emergence of cancer in multicellular organisms. We argue that proliferation of 'profiteering phenotypes' is often an emergent property of disturbed, resource‐rich environments at all scales of biological organization. We review the evidence for this phenomenon, explore it within the context of malignancy, and discuss how this ecological framework may offer a theoretical background for novel strategies of cancer prevention. This work provides a compelling argument that the traditional separation between medicine and evolutionary ecology remains a fundamental limitation that needs to be overcome if complex processes, such as oncogenesis, are to be completely understood.